(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2020)
Multi-phenyl structured random polymer was synthesized via condensation polymerization reaction by applying different monomer ratios and characterized by various spectroscopic methods (FT-IR, 1H NMR). The prepared polymers showed good thermooxidative stability up to 400 ºC. The surface morphology was studied by FESEM that showed the good linkage among the polymer chains. The EDS data of poly(fluorenylene ether ketone), PFEK; demonstrated that all the monomers participated in the copolymerization reaction. Inherent viscosity values of the polymers were obtained in the range of 0.76∼1.12 dL g-1. The polymers’ yield was within 85 90%. The obtained results indicate that the multi-phenyl structured polymer will be the good candidates to prepare the effective aromatic hydrocarbon polymer electrolyte membrane. Bangladesh J. Sci. Ind. Res.55(2), 139-146, 2020